Current dilemmas in the pathological staging of colorectal cancer: the results of a national survey. Issue 4 (5th November 2020) - Wong, Newton A C S; Bracey, Tim S; Mozayani, Behrang; Bateman, Adrian C; Novelli, Marco R; Shepherd, Neil A
Abstract : Aims: Accurate and consistent pathological staging of colorectal carcinoma (CRC) in resection specimens is especially crucial to guide adjuvant therapy. The aim of this study was to assess whether certain staging scenarios yield discordant opinions in the setting of current international and UK national guidelines. Methods and results: Members of the UK Gastrointestinal Pathology External Quality Assurance Scheme were invited to complete an anonymous, on‐line survey that presented 15 scenarios related to pT or pR staging of CRC, and three questions about the respondent. The survey invitation was e‐mailed to 405 pathologists, and 184 (45%) responses were received. The respondents had discordant opinions on whether and how CRC pT or pR staging is affected by: acellular mucin lakes and duration after short‐course radiotherapy; the nature of the carcinoma at a resection margin or peritoneal surface; and microscopic evidence of perforation. This discordance was rarely related to the respondent's occupation type, and was not related to duration of work as a consultant or the staging guidelines used. Conclusions: This survey confirms that there remain several clinically critical but unresolved pT and pR staging issues for CRC. These issues therefore deserve attention in future versions of international and national staging guidelines.